African sacred spaces culture, history, and change - Ogundayo, 'BioDun J., 1957-; Adekunle, Julius (Lexington Books, 2019)
This book focuses on space in African and Black religion and spirituality through the lenses of area studies, African and black diaspora studies, history and culture, cultural studies, ecotourism, environmentalism, and sustainability--Provided by publisher.